(untitled) (Scientific journal of the Fergana State University, 2024)
This article describes the role of onomastics in linguistics, its relationship with other fields, and the analysis of research on these units. It is said that the study of the characteristics of the formation is of great scientific importance. Also, the structural-semantic study of anthroponyms in Uzbek and English languages and the specific features of the motifs of these units are proved with the help of examples. The theoretical information and views of the researchers conducting scientific research on the directions of anthroponymics of uzbek and english linguistics were studied.